1994
DOI: 10.1093/fampra/11.3.292
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Waiting Room Notice-Boards as a Vehicle for Health Education

Abstract: To determine whether patients read and remembered health promotion messages displayed in waiting rooms, 600 patients in a UK general practice were given a self-complete questionnaire. Two notice-boards carried between 1 to 4 topics over four study periods. Three-hundred and twenty-seven (55%) of subjects responded. Twenty-two per cent recalled at least one topic. Increasing the number of topics did not increase the overall impact of the notice-boards. The numbers of patients recalling a topic remained constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 0 publications
0
32
1
1
Order By: Relevance
“…However, 25% reported that the posters raised more questions than they answered. Contrasting with the two studies above, Wicke et al (1994) found that only 22% of patients at a rural practice recalled at least one general health topic posted on a notice board display, and less than 10% of patients read or picked up health leaflets. In addition, Ashe et al (2006) found that educational posters had no significant impact on target health behavior (antibiotic overuse).…”
Section: Introductioncontrasting
confidence: 75%
“…However, 25% reported that the posters raised more questions than they answered. Contrasting with the two studies above, Wicke et al (1994) found that only 22% of patients at a rural practice recalled at least one general health topic posted on a notice board display, and less than 10% of patients read or picked up health leaflets. In addition, Ashe et al (2006) found that educational posters had no significant impact on target health behavior (antibiotic overuse).…”
Section: Introductioncontrasting
confidence: 75%
“…One study showed that in the United Kingdom, adult patients rarely read or took home information handouts left in waiting areas, although they were found to read and recall short messages on waiting room bulletin boards. 46 In a related study, information handouts sent through the mail in conjunction with a media campaign (to reduce risk for malignant melanoma) were more effective than were informational handouts mailed alone. 47 This suggests that patient awareness of and interest in a particular topic is essential for handouts to be effective teaching tools, emphasizing the concept of a teachable moment.…”
Section: Information Handoutsmentioning
confidence: 99%
“…Printed educational materials are commonly offered in waiting rooms, but their efficacy has been shown in studies to be highly variable, and dependent upon the specific contexts, populations, and formats involved [10,13,21]. Beyond printed materials, there has been a lack of innovative approaches to education in the waiting room that both robustly utilize available technologies and also attempt to reach underserved groups [9].…”
Section: Introductionmentioning
confidence: 99%